Gas void formation in statically cooled waxy crude oil - Chala, G.T. (Elsevier Masson SAS, 2014)
If a gel is formed when the flow of waxy crude oil within a pipeline is stopped for a period of time, the required restart pressure may be high and the line is costly to operate. The conventional method of predicting the restart pressure for gelled crude oil assumes a constant yield stress across and along the pipe section; this often leads to excessive over sizing of pump and piping system. Many researches highlighted that the presence of gas voids upon cooling of waxy crude may have an impact on the yield stress of gelled crude. This paper describes the use of Magnetic Resonance Imaging (MRI) to investigate the formation behaviour of gas voids within a gelled crude oil sample from a field in the South China Sea. Scanning of gelled crude at selected temperatures was performed following cooling in the circular pipe section within an experimental flow loop rig. Gas voids within the range of 7-12 were observed in the gelled samples resulted from different cooling temperatures and cooling rates. The cooling temperature and cooling rates were observed to influence significantly the location and volume of gas voids formed within the gelled samples. Higher cooling rates resulted in higher volume of gas voids close to pipe wall while lower cooling rates resulted in more gas voids located around core of the pipe. Â© 2014 Elsevier Masson SAS. All rights reserved.